Prices versus Nudges: What Matters for Search Versus Purchase of Energy Investments? - Holladay, Scott; LaRiviere, Jacob; Novgorodsky, David; Price, Michael (Journal of Public Economics, 2019)
We report the results of a field experiment where we exogenously vary the use of social comparison “nudges” and subsidies for participation in an in-home energy audit program. We follow subjects through to subsequent purchase of durable goods. We therefore can compare the causal effect of financial incentives and nudges along two margins: audits, which we liken to search, and purchase of durables. Using data on nearly 100,000 households we document that both prices and nudges cause a statistically significant increase in audits. Comparing point estimates, effective nudges are worth roughly 50–70. However, we find that neither nudges nor subsidies do not significantly impact installations.